2007
DOI: 10.1073/pnas.0610444104
|View full text |Cite
|
Sign up to set email alerts
|

CXCR7 (RDC1) promotes breast and lung tumor growth in vivo and is expressed on tumor-associated vasculature

Abstract: Chemokines and chemokine receptors have been posited to have important roles in several common malignancies, including breast and lung cancer. Here, we demonstrate that CXCR7 (RDC1, CCX-CKR2), recently deorphanized as a chemokine receptor that binds chemokines CXCL11 and CXCL12, can regulate these two common malignancies. Using a combination of overexpression and RNA interference, we establish that CXCR7 promotes growth of tumors formed from breast and lung cancer cells and enhances experimental lung metastase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

38
580
3
3

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 496 publications
(624 citation statements)
references
References 22 publications
(30 reference statements)
38
580
3
3
Order By: Relevance
“…It is is consistent with previous breast cancer studies showing that the CXCL12 /CXCR7 axis supports cancer cell growth (Wani et al, 2014). The mechanisms and signaling pathways involved in CXCL12/CXCR7 have been reported in pancreatic cancer and the results indicated that CXCR4 and CXCR7 signaling is b-arrestin-2-dependent and controls CXCL12 signals to the MAPK/AKT pathway (Miao et al, 2007).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…It is is consistent with previous breast cancer studies showing that the CXCL12 /CXCR7 axis supports cancer cell growth (Wani et al, 2014). The mechanisms and signaling pathways involved in CXCL12/CXCR7 have been reported in pancreatic cancer and the results indicated that CXCR4 and CXCR7 signaling is b-arrestin-2-dependent and controls CXCL12 signals to the MAPK/AKT pathway (Miao et al, 2007).…”
Section: Discussionsupporting
confidence: 91%
“…The direct effect of CXCL12/CXCR7 in breast cancer metastasis is that CXCR7 recruits tumor-promoting macrophages to the tumor site through regulation of the macrophage colony-stimulating factor/macrophage colony-stimulating factor receptor signaling pathway. In addition, CXCR7 regulated breast cancer metastasis by enhancing expression of metalloproteinases (MMP-9, MMP-2) and vascular cell-adhesion molecule-1 (Miao et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…The full extent of the importance of CXCR7 signaling in development and adult function remains to be determined. (Miao et al, 2007;Sierro et al, 2007;Valentin et al, 2007).…”
Section: The Chemokine Familymentioning
confidence: 99%
“…These include deficits in β-lymphopoiesis and myelopoiesis (Nagasawa, 2007;Nagasawa et al, 1996;Nie et al, 2004;Zou et al, 1998), cardiogenesis (Miao et al, 2007;Nagasawa et al, 1996;Zou et al, 1998), angiogenesis (Tachibana et al, 1998;Zou et al, 1998), neurogenesis (Lu et al, 2002;Stumm et al, 2003;Tran et al, 2007) and germ cell migration and development (Dumstrei et al, 2004). Basically, all of these phenotypes can be explained by the observation that CXCR4 signaling is important in regulating the migration of different types of stem/ progenitor cells.…”
Section: The Chemokine Familymentioning
confidence: 99%
“…8 A second receptor for CXCL12, CXCR7 has only most recently been identified and has been implicated in tumor growth and metastasis. [9][10][11] Elevated levels of CXCL12 were found in patients with multiple sclerosis, inflammatory myopathies, spondyloarthropathies and RA. [12][13][14][15][16][17] Levels of CXCL12 in the synovial fluid of RA patients are around 10 times higher than in healthy joints and reach a mean of 750 ng ml À1 .…”
Section: Introductionmentioning
confidence: 99%